(untitled) (Global Journal of Human-Social Science, 2013)
By extending the findings of Hu s 2001 investigation on how socio-psychological variables and EFL students English language proficiency are related this study examines the demographic significance between different target groups and the subsequent implications towards predictions of EFL proficiency thereby further assisting EFL practitioners Stepwise multiple regression analyses reveal that as the predominant factor self-confidence accounts for 39 of the variance in determining the prediction of English language proficiency among Taiwanese students in a technological institute This finding contrasts with that of Hu 2001 in which motivation accounts for the largest determinant among Taiwanese university students University students slightly outperform technological institute students Hu 2007 2011 in terms of either academic performance or English language proficiency attainment This phenomenon further diminishes the self-confidence of the technological institute students ultimately hindering their attempts to increase English language proficiency For EFL students in a technological institute self-confidence profoundly impacts their attainment of English language proficiency